Understanding Railway Trespassing in a South African City: The Case Of Cape Town - Williams, Faizel (Department of Civil Engineering, 2021)
Trespassing behaviour is a problem for railway operations and manifests itself through train-pedestrian collisions, incidents of theft and vandalism to rail infrastructure, as well as encroachment on railway property. The study has consisted of a quantitative and a qualitative part. The quantitative part analyses demographic, temporal and spatial data on train-pedestrian fatalities and injuries, as well as data on occurrences of theft and malicious damage to rail infrastructure in the Cape Town Functional Region between 2015 and 2018. The qualitative part presents the perspective from a diverse group of subject matter experts, having explored opinions on trespassing behaviours and preventative measures. Additionally, the trespassing behaviour at several sites was investigated and a case study evaluation of the efficacy of a pilot Rail Enforcement Unit was carried out. There were 456 railway-related deaths during the study period with 330 of this being train-pedestrian collisions. There were 4715 occurrences of theft and malicious damage to railway assets over the period. Several hot-spot areas were identified via the data and interviews with experts and several sites chosen for further verification. Site visits confirmed widespread trespassing behaviours with the two worst locations recording an average of over 300 persons in a 15-minute period. The case study reviewing the effectiveness of the security and enforcement countermeasure revealed that occurrences of train-pedestrian incidents, as well as security occurrences have increased by 1.4% and 7.5% respectively. Evidence of geographical displacement of crime is evident, suggesting that enforcement countermeasures are temporarily effective and need to be considered in combination with other measures to ensure its durability. In conclusion, this research presents a detailed analysis of railway trespassing and its main effects in order to understand the problem locally. Different approaches are required to combat the various guises of railway trespassing. Certain countermeasures may well be within the rail operator's remit, but essentially, the nature of problems experienced by the rail operator is beyond a rail problem, and requires a systems approach involving multiple authorities